Pharmacokinetic-pharmacodynamic modeling of metoprolol stereoisomers in spontaneously hypertensive rat - Yin Xiao-Xing; Zhang Yin-Di; Luo Jian-Ping; Huang Xiao-Ping; Shen Jian-Ping; Ding Yong; Huang Da-Kuang (Acta Pharmacologica Sinica, 2016)
AIM: To study the combined pharmacokinetic-pharmacodynamic (PK-PD) model of metoprolol stereoisomers, and compare their inhibitory effects on cardiovascular system in the spontaneously hypertensive rats (SHR). METHODS: The drug concentration in plasma was measured by the reversed phase HPLC and the drug effects were recorded by polygraph. The pharmacokinetic parameters and the PK-PD model parameters were calculated. RESULTS: The plasma concentration-time profiles were adequately described by two-compartment model. Differences of Vd between (+)-Met and (-)-Met were found. The relationships between effects and concentration of effect compartment were represented by the sigmoid-Emax model. The Css50 of Vmax, dp/dtmax, and HR inhibitory effects of (+)-Met were larger than those of (-)-Met. CONCLUSION: Stereo-selective drug distribution and different potencies of the inhibitory effects of (+)-Met and (-)-Met existed in SHR.